rucepherdy
rucepherdy
20-12-2016
Mathematics
contestada
Solve for x.
3(-2x - 1) = 2(x + 5)
Respuesta :
Аноним
Аноним
20-12-2016
Hello :),
3(-2x-1)=2(x+5)
-6x-3=2x+10
-6x-2x=10+3
-8x=13
x=13/-8=-1,625
Answer Link
VER TODAS LAS RESPUESTAS ( 86+ )
Otras preguntas
What ideas and inventions encouraged Europeans to begin overseas exploration?
What is the least amount of money that rounds to 105.40
What are the solutions of the equation? -20 = |b|/-5 Choose ALL answers that are correct. A. -100 B. -4 C. 4 D. 100
Which of the following statements about air pollution is not true? a. Air pollution is caused by natural and human processes. b. Carbon monoxide and sulfur o
is 6 players to one ball a ratio
how can you show that two objects are proportional with a graph?
Which statements are true according to the order of operations? Choose exactly two answers that are correct. a. 32+8÷4=40÷4=10 b. 4+12÷2=4+6=10 c. (20–5)•3=1
What is the prefix of inhospitable?
what is 8725 w=10619
Which of the following items demonstrates an important relationship between African and European civilizations during the classical era?
ACCESS MORE